Comparative Study on the Physio-Biochemical Responses of Spring and Winter Barley Genotypes under Vernalized and Greenhouse Conditions - Adeela Rasheed; Qidong Feng; Muhammad Faheem Adil; Muhammad Ahsan; Zhigang Han; Fanrong Zeng; Imran Haider Shamsi (Agronomy, 2022)
In barley (Hordeum vulgare L.) breeding, heading date is one of the most important agricultural traits that is essential for the completion of its life cycle. Certain endogenous and environmental factors regulate floral transition, morphing the complex genetic mechanism of the heading phase, which could serve as a premise of orchestration for improved yields. To elaborate the network of genetic and environmental signals, a hydroponic experiment was carried out using two spring (i.e., DM65 and DM70) and two winter barley genotypes (i.e., DM269 and DM385). Our results confirmed that the vernalized environment produced a substantial reduction in plant height, biomass and photosynthetic activity compared with the control plants. A noticeable increase in oxidative stress was exhibited by DM65 and DM70 plants compared with their respective controls at 20 °C, while no significant difference was observed for any genotype grown in the greenhouse (25 °C). Simultaneously, increased antioxidant enzyme activity in winter barley genotypes showed a defensive mechanism under vernalized conditions (4 °C). Furthermore, the expression of key regulatory flowering genes revealed that the vernalization gene (HvVRN1) is the key regulator of floral induction after cold exposure, whereas Photoperiod Response Locus 1 (HvPpd-H1) had significantly higher expression under greenhouse conditions, along with Phytochrome C (HvPHY-C), validating their involvement as upstream heading time regulators. These findings contribute to enriching the study of environmental signals that substantially modulate the complex mechanism of barley heading date.